An acyclic aluminyl anion. Issue 35 (14th April 2023) - Jackson, Ross A.; Matthews, Aidan J. R.; Vasko, Petra; Mahon, Mary F.; Hicks, Jamie; Liptrot, David J.
Abstract : The potassium aluminyl, K2 [Al{N(Dipp)SiMe3 }2 ]2 has been synthesised. Reaction with [HC{(CH3 )C(Dipp)N}2 ]MgI(OEt2 ) forms [HC{(CH3 )C(Dipp)N}2 ]MgAl{N(Dipp)SiMe3 }2, a monomeric, acyclic, magnesium aluminyl complex. Abstract : The potassium aluminyl complex K2 [Al{N(Dipp)SiMe3 }2 ]2 was synthesised via reduction of [AlI{N(Dipp)SiMe3 }2 ] (Dipp = 2, 6-i-Pr2 C6 H3 ). This represents the first example of an aluminyl anion supported by an acyclic ligand framework. Attempts to yield the same structure with a larger ligand framework, {N(Dipp)Si(i-Pr)3 }, led to C–H cleavage. K2 [Al{N(Dipp)SiMe3 }2 ]2 behaves as a nucleophilic source of aluminium; reaction with an electrophilic β-diketiminate supported magnesium(ii ) iodide forms a monomeric, acyclic magnesium aluminyl complex.